JAKARTA EVOLUTION (JAKEVO) APPLICATION INNOVATION IN ONLINE LICENSING SERVICES IN DKI JAKARTA - Lydia, Angelia Devika; Tukiman, Tukiman (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2024)
Public service innovation is the main focus to improve the quality of services for the community, especially in terms of licensing services. One of the applications of licensing innovation is by launching the Jakarta Evolution (JakEVO) application to facilitate the online licensing process at the DKI Jakarta Investment and One-Stop Integrated Services Office. The purpose of the research is to determine the innovation of the JakEVO application in online licensing services at the Capital Investment Office and One-Stop Services of DKI Jakarta. This study uses descriptive qualitative research method the results of the study show that: 1) Relative Advantage, the JakEVO application provides benefits for the community and ease of obtaining when accessing permits. 2) Conformity, JakEVO is declared inappropriate because the flow of handling permits and the time of handling permits are different from the provisions that apply to the Decree of the Head of the DKI Jakarta PTSP Office. 3) Complexity, the level of complexity of JakEVO according to users is quite complicated. 4) Trialed Ability, before being launched to the community JakEVO did not go through the trial stage. 5) Observability, this application is easily observed by the public to monitor the course of permit files and make it easier for officers to get detailed data on the number of permits entered in the application from 2020 to 2023, so the JakEVO application has not been able to improve online licensing services in DKI Jakarta.